Assessing Senior High School Science Students’ Planning Skills In Selected Topics From The Integrated Science Syllabus - Naah, Anna M.; Peter Mayeem, Bilatam; Adjei, Augustine; Ossei-Anto, Aquinas (International Journal of Scientific Research and Management (IJSRM), 2018)
The study was conducted to assess Senior High School Science Students’ proficiency level in planning practical activities for ‘Test of Practical’ with selected topics from the Integrated Science syllabus. A total of 180 respondents (90 male and 90 females) out of a population of 1029 were sampled from three senior high schools in the Municipal Education, Offinso. Computer generated random numbers were used to randomly select 30 males and 30 females from each school in the municipality. The study employed the performed task instrument. Three tasks on planning were developed with their scoring formats and scoring details. Task A was on ‘distillation’. Task B on ‘density’ and task C on ‘osmosis’. A pilot test was conducted in one of the seniorhigh technical schools in the Atwima Nwabiagya District Educationand the response dichotomously scored, internal reliabilityof the various tasks was assessed using Kuder Richardson 20. The reliability of the various tasks obtained were task A, (0.731); B, (0.945); and C, (0.86). the data obtained for the actual study were statistically analyzed using descriptive, (percentages and means) inferential statistics (Independent t-test and Analysis of variance(ANOVA)). The students exhibitedhigh proficiency on the planningskills. There were many similarities between the performances of female and male students of the various schools. The performance of students of school A were statistically significantly different fromschools B and C on task B. from the major findings of this study, it is recommended that ‘Test of Practical’ questions should be related to  real life situations